Knowledge of patients with diabetic foot syndrome - Michałek-Kowalczyk, Magdalena; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
Aim: The aim of the study was to assess the knowledge of patients with diabetes and diabetic foot syndrome. Material and methods: Study was performed among 25 patients treated due to diabetic foot syndrome and 25 patients with diabetes with no complications. Fourteen women and 36 men were included into the study, age range was 26 to 82 years, mean age 60,8 years. The studied groups of patients differed statistically significantly when considering risk factors of DFS, knowledge of treatment options, self-monitoring and proceeding in case of complications. Study was performed personally based on patient’s history and self-made questionnaire. Patient’s knowledge about diabetes and self-care was assessed in detail. Statistical analysis was performed by STATISTICA software version 6.0. Results: Our study found that patients with DFS had worse state of knowledge. All patients without DFS had a glucometer and used it properly, they were performing measurements on time, and they were noting the results of the measurements and were making regular calibrations of the device. Whereas patients suffering from DFS were performing these activities certainly more rarely, what was statistically significant p<0.05. Additionally patients with DFS were controlling glucose value statistically significant more rarely in comparison to patients without the disease. Diabetics with DFS dispose lower state of knowledge about proper glucose levels, principles of correction of antidiabetic medicine doses or about most common acute complications of increased or decreased blood glucose levels. Patients with DFS significantly more often (p<0.001) do not know principles of diabetic diet, do not perform specific types of diet (p<0.05), more rarely keep diet and modify it (p<0.001). Knowledge about foot care among my patients is also lower in DFS population (p<0.001). Conclusion: 1. The comparison of health problems between patients with diabetes mellitus and patients with diabetic foot syndrome revealed that first group of patients has better knowledge about the disease. 2. Patients with DFS are characterized by worse physical activity, higher blood glucose levels before and after meals, insufficient self-control, lower state of knowledge about their disease, unbalanced diet, low state of knowledge about proper foot hygiene and inspection, lack of performing proper, regular foot care and self-monitoring. 3. Patients with diabetic foot disease have lower state of knowledge about risks and methods of avoidance of these complications in comparison to the other diabetic patients.